Seroprevalence and risk factors for Hepatitis B and C among health care workers - Anwar, Manal Mohamed; Ahmed, Doaa; Sheemy, Mostafa; El-Tayeb, Mohamed (International Journal of Infection Control, 2017)
Health care workers (HCWs) are at high risk of exposure to Hepatitis B & C virus transmission due to injuries and frequency of exposure. We aimed to assess seroprevalence of hepatitis B and C infection among nurses and housekeepers in Beni-Suef university hospital, and to identify possible risk factors. A cross sectional study was conducted from March to July 2016 using a self-administered questionnaire. A blood sample was withdrawn from each participant and was tested for hepatitis B surface antigen (HBsAg) and anti-HCV antibodies. ELISA seropositivity to HCV was confirmed by PCR. The study involved 175/255 participants with a response rate of 68.5%. Nurses constituted 76% and 24% were housekeepers. Overall prevalence of HCV seropositivity was 4.6%; detected by “ELISA". Confirmatory PCR testing revealed positivity in 75% (6/8) of them. Cut injuries was a risk factor for HCV positivity (OR 4.388, 95% CI 0.859 - 22.4, P= 0.05). Previous training and use of gloves was a protective factor (OR 0.135, 95% CI .016- 1.118, P= 0.03 and OR 0.241, 95% CI 0.055- 1.04, P= 0.04 respectively). None of the participants were found to be HBV seropositive. Practices and behaviours posing risk for HCWs included needle stick injury (NSI) and cut injuries. Focus on improving safety training programs to HCWs and provision of infection prevention equipment is needed. In addition regular reporting, follow up and assessment of occupational exposures should be in place.